2018
DOI: 10.1093/gji/ggy017
|View full text |Cite
|
Sign up to set email alerts
|

Multimode seismoelectric phenomena generated using explosive and vibroseis sources

Abstract: A field trial of seismoelectric surveying was carried out at a site underlain by 20 m of water-saturated clayey Champlain Sea sediments, renowned for their amenability to high resolution imaging by seismic reflection surveys. Seismically induced electrokinetic effects were recorded using an array of 26 grounded dipole electric field antennas, and two different seismic sources including an eight-gauge shotgun, and a moderate power (10 000 lb Minivib) vibrator. Despite the high electrical conductivity of the sed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
34
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(40 citation statements)
references
References 64 publications
6
34
0
Order By: Relevance
“…These signals are interfacial radiation EM waves induced by nearly normal incidence of seismic waves on the porous media's interface, that is, the free surface of this water-saturated half-space model. Such kind of interfacial radiation EM waves have been confirmed in both numerical simulation (e.g., Haartsen and Pride 1997;Garambois and Dietrich 2002) and field experiment studies (e.g., Butler et al 2018).…”
Section: Water-saturated Half-space Porous Modelmentioning
confidence: 64%
See 3 more Smart Citations
“…These signals are interfacial radiation EM waves induced by nearly normal incidence of seismic waves on the porous media's interface, that is, the free surface of this water-saturated half-space model. Such kind of interfacial radiation EM waves have been confirmed in both numerical simulation (e.g., Haartsen and Pride 1997;Garambois and Dietrich 2002) and field experiment studies (e.g., Butler et al 2018).…”
Section: Water-saturated Half-space Porous Modelmentioning
confidence: 64%
“…They pointed out that, in retrospect, evanescent EM waves had been observed in earlier seismoelectric field trials, but not recognized correctly. The recognition of seismoelectric evanescent EM waves helps explain the origin of similar effects reported in previous studies and will contribute to improved interpretation of seismoelectric records (Butler et al 2018). In addition, evanescent EM waves can be a new form that the electrokinetic effect may take in practical application (Dietrich et al 2018).…”
Section: Introductionmentioning
confidence: 61%
See 2 more Smart Citations
“…Garambois & Dietrich (2002) showed that IRs are developed over a Fresnel zone that is positioned directly beneath a source located at the Earth's surface. However recent studies suggest that for incident angles larger than the critical angle θ c = arcsin(v seis /v EM ), so called evanescent IRs are excited (Ren et al 2015(Ren et al , 2018Butler et al 2018). The evanescent IRs are carried along the interfaces by the seismic waves and can therefore be detected further away from the source.…”
Section: S E I S M O E L E C T R I C S P E C T R a L R At I O Smentioning
confidence: 99%